(3MGTjI Ydi TQM GdSLGhfOjI aj GdaQGFV ddLQLGfjs - (3GdaQVj, MSf GdQhej CejQ, J (B941 (3g`s ((3HdOI CSchHs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO def UjQ GdYdeGA hQKI GdCfHjGA hbOQ ef GdCehGJ SgGe CMjGA GdChdjGA hYjf HeTjFJg CUMGH GdaQGjV hGdYUHGJ def jaJj aMOGfj Pdc eSJeOG ef QhMGfjJg Edi Gf CbQQ ebGUOg hCMQQ YhGjOgs
(3BNQgG (B:s
(3aSei Pdc MQH Uajf hGdPj GJab Ydjg Cgd GdMb gh Gf GdMb aj LejY Pdc eY Ydj QVj Gddg Yfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 552s
(3cTa GdXfhf (B2 / 1248s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdaQGFVs